God Head : A Novel - Cline, Leonard, 1893-1929 (Book collections on Project MUSE., 2012)
"Lavished with praise at the time of its 1925 publication, Leonard Cline's phantasmagoric God Head is being republished so a new generation of readers can marvel at its dark magic. Cline's mesmerizing debut follows the journey of Paulus Kempf, a fugitive labor agitator who takes refuge with a colony of Finns on the remote shores of Lake Superior in the upper peninsula of Michigan. Kempf, a former surgeon, poet, writer, sculptor, and hyper-intellectual, is at first deeply impressed by the folklore and traditions of the quiet, gentle Finns, not to mention their generosity and hospitality. But he soon begins to play upon their superstitions and exploits their kindness through the power of his cunning and imagination, manipulating them into seeing him as a kind of a god. As Cline's novel hurtles toward its unforgettable climax, Kempf's capacity for compassion or mercy swiftly falls to the wayside as he seduces his host's wife and then murders the man in cold blood. Soon thereafter he carves a giant God Head into the side of a nearby mountainside, which the villagers look upon with awe and fear, held in the thrall of Kempf's mysterious intimations of its malicious power. Having achieved complete domination over the Finns, Kempf ultimately tires of their gullibility and returns to civilization, his quest for self-mastery complete. God Head's descent into the dark void of the human heart will thrill modern readers who are sure to cherish this lost literary artifact from the shadow canon of American fiction"--